A method for meta-analysis of molecular association studies - Ammarin Thakkinstian (2018)
Although population-based molecular association studies are becoming increasingly popular, methodology for the meta-analysis of these studies has been neglected, particularly with regard to two issues: testing Hardy-Weinberg equilibrium (HWE), and pooling results in a manner that reflects a biological model of gene effect. We propose a process for pooling results from population-based molecular association studies which consists of the following steps: (1) checking HWE using chi-square goodness of fit; we suggest performing sensitivity analysis with and without studies that are in HWE. (2) Heterogeneity is then checked, and if present, possible causes are explored. (3) If no heterogeneity is present, regression analysis is used to pool data and to determine the gene effect. (4) If there is a significant gene effect, pairwise group differences are analysed and these data are allowed to 'dictate' the best genetic model. (5) Data may then be pooled using this model. This method is easily performed using standard software, and has the advantage of not assuming an a priori genetic model. Copyright © 2004 John Wiley & Sons, Ltd.